2019
DOI: 10.3319/tao.2018.11.15.01
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-event analysis of the 2018 ML 6.2 Hualien earthquake using source time functions

Abstract: Through forward multiple-event analysis of teleseismic P-waves using source time functions (STFs), derived by non-negative time-domain deconvolution, we inferred the rupture features of the 2018 Hualien earthquake. At least six sub-events composed the Hualien earthquake, with the largest one (corresponding to M w = 6.3) occurring 4.8 s later than the initiation of rupture. The total seismic moment (M 0 ) of 6.48 × 10 18 Nm (M w = 6.5) and radiated seismic energy (E S ) of 1.76 × 10 14 Nm led to the E S /M 0 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…2, our results revealed that the largest subevent with MW 6.1 occurred about 3 s later than the initiation. The 𝐸 𝑠 /𝑀 0 ratio of 3.4  10 −5 also resembled the global average (3.0  10 −5 ; Ide & Beroza 2001) and was comparable with that of the 2018 Hualien earthquake (2.72  10 −5 ;Hwang et al 2019).…”
supporting
confidence: 58%
“…2, our results revealed that the largest subevent with MW 6.1 occurred about 3 s later than the initiation. The 𝐸 𝑠 /𝑀 0 ratio of 3.4  10 −5 also resembled the global average (3.0  10 −5 ; Ide & Beroza 2001) and was comparable with that of the 2018 Hualien earthquake (2.72  10 −5 ;Hwang et al 2019).…”
supporting
confidence: 58%
“…On 6 February 2018, an earthquake with a moment magnitude (M w ) of 6.4 hit Hualien, east Taiwan, toppling several buildings and causing more than a dozen casualties Chen et al 2019;Hwang et al 2019;Wen et al 2019). Unlike another hazardous M w = 6.4 earthquake that occurred two years ago in Meinong, Southwest Taiwan (Kanamori et al 2017;Kuo-Chen et al 2017;Lee et al 2017), the 2018 Hualien earthquake was preceded by a prominent foreshock sequence, including a M w = 6.1 event followed by more than 50 events of local magnitude M L ≥ 3.0 within 12 h that migrated southwest and upwards (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…b E S fromVenkataraman and Kanamori (2004) c E S fromHwang (2012) d E S from the IRIS DMC (2013) e E S fromHwang et al (2019) f E S fromHwang et al (2022) g E S , M 0 and M W from this study…”
mentioning
confidence: 82%
“…Similarly, from the 2019 Xiulin aftershocks, the logE S -M L relationship, analyzed by Chan et al (2020), also failed to predict the E S of the 2019 M L 6.3 Xiulin earthquake (mainshock). Figure 3 also illustrates the E S values for several M L > 6 earthquakes in Taiwan (Venkataraman and Kanamori 2004;Wang, 2004;Hwang 2012;Hwang et al 2019Hwang et al , 2022; Table 1).…”
Section: E S Versus M Lmentioning
confidence: 99%
See 1 more Smart Citation